Relationship Between Medical Students’ Empathy and Occupation Expectation: Mediating Roles of Resilience and Subjective Well-Being - Wu, Wenzhi; Qi, Qiqi; Cao, Xin; Li, Shujun; Guo, Zhichao; Yu, Lei; Ma, Xiao; Liu, Yilin; Liu, Zijun; You, Xu; Chen, Yatang; Long, Qing; et al. (Frontiers in Psychology, 2021)
Background: The occupation expectation of medical students can predict the possibility of their future employment in the medical industry, and empathy is the special ability of medical students in their study and career, which affects the development of their occupation expectation. Objective: To explore the relationship between resilience and subjective well-being between medical students’ empathy and occupation expectation and their internal mechanisms. Design: Data were collected from October 2020 to March 2021 using a paper questionnaire survey. Subjective: 586 medical students at a key medical university in Yunnan Province were invited to complete the survey. Main Measures: The Basic Empathy Scale, Connor-Davidson Resilience Scale, Subjective Well-Being Questionnaire, and Occupation Expectation Scale. Key Results: The empathy is intended to affect the occupation expectation of medical students through four paths. The direct path effect value is 0.073 (95% CI: 0.007∼0.217), the indirect path 1 effect value is 0.078 (95% CI: 0.022∼0.134), indirect path 2 effect value is 0.010 (95% CI: 0.005∼0.022), indirect path 3 effect value is 0.022 (95% CI: 0.0604∼0.039), all the confidence intervals do not contain 0, and the mediated effect ratio is 60.109%. Conclusion: Empathy has an impact on occupation expectation of medical students through the sequential mediating effects of resilience and subjective well-being. Medical colleges should fully consider the role of protective factors when cultivating and enhancing the occupation expectation of clinical medical students. Strengthening the intervention of emotional factors (empathy), self-regulating ability (psychological toughness) and cognitive factors (subjective well-being) is an important way to effectively establish professional values, improve occupation expectation of medical students and reduce the turnover rate of medical students.